Brand Management Practices, Corporate Image, Customer Characteristics and Satisfaction among University Students in Kenya - Stephen Maorei; Justus Munyoki; Mary Kinoti; Joseph Owino (European Scientific Journal, ESJ, 2019)
The objective of the study was to determine the influence of brand management practices, corporate image, and customer characteristics on customer satisfaction among university students in Kenya. The study was founded on three theories namely: Customer based brand equity model, expectation confirmation theory and consumer utility theory. The study adopted descriptive research design, the target population comprised of students fromall 70 universities registered and accredited to operate in Kenya, with a population of 443,783 students enrolled for various undergraduate degree programmes from which a sample of 384 students was drawnstudent’s characteristics in public and private universities tend to differ significantly. The study used a multistage sampling procedure that involved two stages. The first stage was sampling 30% of the universities in each category using a simple random sampling method. The second stage used systematic random sampling, selecting every 5th student entering the main gate of the main campus of the selected university. Purposeful sampling was applied strategically to ensure equitable distribution of respondents based on gender, the program enrolled and the year of study. This helped reduce biasness and ensured fair representation. Data was analyzed using descriptive statistical analysis, correlation analysis and regression analysis. The study revealed there was a joint effect of brand management practices, customer characteristics and corporate image on customer satisfaction in university students in Kenya with R2=0.308; p-value= 0.000. Brand management practices were found to influence customer satisfaction more in the private individual owned and private institutional owned than in public universities, with R square of 0.149, 0.312 and 0.423 respectively. Similarly, corporate image was found to have a stronger moderation effect on the relationship between brand management practices and customer satisfaction in private institutional owned universities as compared to the private individual owned and public universities, with R2 of 0.671, 0.440 and 0.213 respectively. The study recommends that policy can be developed that encourages inculcating brand management practices within universities in Kenya. Policy can be developed to encourage measurement and reporting of performance along brand management practices as used in this study.